Heat‐Shrinkable Electrospun Fibrous Tape for Restoring Structure and Function of Loose Soft Tissue. (26th October 2020) - Saiding, Qimanguli; Jin, Jing; Qin, Menglu; Cai, Zhengwei; Lu, Min; Wang, Fei; Cui, Wenguo; Chen, Xinliang
Abstract: Non‐invasive recovery of loose soft tissue caused by trauma, organ expansion, or compression has not been solved properly. Herein, a new approach of heat‐shrinkable electrospun fibrous tape (HS‐EFT) is constructed via electrospinning in which the contraction of the poly(lactic‐co‐glycolic acid) HS‐EFT causes the relaxed fascia to pull back at body temperature while the mechanical force of retraction is transformed into an external signal that regulates the behavior of fibroblasts. As it contracts more than 40% within five days, the fast proliferation of fibroblasts on the contracted fibrous membrane is observed followed by the formation of more stress fibers, consequently promoting the nuclear transfer of mechanical stimulation‐sensitive co‐transcriptional molecule, yes‐associated protein (YAP), and eventually making new extracellular matrix (ECM) deposition, as well as tissue strengthen. Moreover, in the process of fascia defect repairing in rabbits, the loose tissue is gathered by fibrous tape which ends in a reduced wound area as well as tissue repairing. Therefore, the HS‐EFT provides great inspiration for the reconstruction of relaxed soft tissue both structurally and functionally in a non‐invasive way. Abstract : A heat‐shrinkable electrospun fibrous tape is fabricated and contracted slowly, retracting the loose tissue regaining normal tissue structure. The retractive force is transformed into mechanical stimulation, which promotes the nuclear transfer co‐transcriptional factor YAP, and eventually making new ECM deposition. The heat‐shrinkable fibrous tape is highly promising for loose soft tissue repair both structurally and functionally.